Kimberlé Crenshaw: The urgency of intersectionality | TED Talk - Crenshaw, Kimberlé (TedTalk, 2016)
Now more than ever, it's important to look boldly at the reality of race and gender bias -- and understand how the two can combine to create even more harm. Kimberlé Crenshaw uses the term "intersectionality" to describe this phenomenon; as she says, if you're standing in the path of multiple forms of exclusion, you're likely to get hit by both. In this moving talk, she calls on us to bear witness to this reality and speak up for victims of prejudice.
Keywords: activisme; afro-féminisme; approches et analyses; com5170; cours; discipline; droit; droits civiques; droits des femmes*; droits humains; féminisme afroaméricain; histoire et politique; intersectionnalité; justice sociale; militance; premier cycle; science politique et droit; thématiques